2019
DOI: 10.1021/jacs.8b12149
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Labeling Reveals Fast Atomic and Molecular Exchange in Mechanochemical Milling Reactions

Abstract: Using tandem in situ monitoring and isotope-labeled solids, we reveal that mechanochemical ball-milling overcomes inherently slow solid-state diffusion through continuous comminution and growth of milled particles. This process occurs with or without a net chemical reaction and also occurs between solids and liquid additives which can be practically used for highly efficient deuterium labeling of solids. The presented findings reveal a fundamental aspect of milling reactions and also delineate a methodology th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 52 publications
(71 reference statements)
0
50
0
1
Order By: Relevance
“…[89] Angewandte Chemie carboxylic and boronic acids using H 2 17 O, [94] while Lukin et al demonstrated rapid deuteration with D 2 O. [95]…”
Section: Benefits Of Solvent-free Environmentmentioning
confidence: 99%
“…[89] Angewandte Chemie carboxylic and boronic acids using H 2 17 O, [94] while Lukin et al demonstrated rapid deuteration with D 2 O. [95]…”
Section: Benefits Of Solvent-free Environmentmentioning
confidence: 99%
“…With aw ise choice of laser parameters and reactants, however, it is possible to follow directm echanocatalysis reaction with both in situ techniques. [33] Both of these methods, however,c an only give indications towards the mechanismso fd irect mechanocatalytic reactions. To fully elucidate the mechanisms, one needs to closer investigate the milling balls urface in the moment of impact.T his on the other hand seems hardly feasible and thus ap roper investigation needs to heavily rely on ex-situd ata.…”
Section: The Mechanismmentioning
confidence: 99%
“…for efficient 17 O‐labeling of hydroxides, oxides, carboxylic and boronic acids using H 2 17 O, while Lukin et al. demonstrated rapid deuteration with D 2 O …”
Section: Improved Selectivity and Reactivitymentioning
confidence: 99%